2020
DOI: 10.1109/tbme.2019.2919488
|View full text |Cite
|
Sign up to set email alerts
|

Sparsity Analysis of a Sonomyographic Muscle–Computer Interface

Abstract: The objectives of this paper are to determine the optimal location for ultrasound transducer placement on the anterior forearm for imaging maximum muscle deformations during different hand motions and to investigate the effect of using a sparse set of ultrasound scanlines for motion classification for ultrasoundbased muscle computer interfaces (MCIs). Methods: The optimal placement of the ultrasound transducer along the forearm is identified using freehand 3D reconstructions of the muscle thickness during rest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 55 publications
3
25
0
Order By: Relevance
“…al. [20] and the results have been corroborated by several studies utilizing wearable ultrasound systems [27], [28]. We intend to confirm our findings with a custom-developed wearable ultrasound imaging system in the future.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…al. [20] and the results have been corroborated by several studies utilizing wearable ultrasound systems [27], [28]. We intend to confirm our findings with a custom-developed wearable ultrasound imaging system in the future.…”
Section: Discussionsupporting
confidence: 85%
“…for sonomyographic gesture recognition applications. [20]. Hence, we believe that a simple equispaced transducer array can be used in most sonomyography-based muscle activity estimation applications.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we plan to use single-element transducers with low-power electronics that could be integrated into a standalone prosthesis socket. Although our prior work suggests that classification accuracy is not reduced with a sparse sensing strategy [41], this has not yet been confirmed in individuals with limb loss. Finally, the sampling rate for EMG was considerably higher than for SMG, so more frames of EMG data were available to train the classifier.…”
Section: Discussionmentioning
confidence: 88%
“…For translation of SMG technology to practical prosthesis sockets, we anticipate utilizing singleelement transducers with low power electronics. Our previous work has indicated that the classification accuracy with sparse sensing is not compromised [56]. However, this result has yet to be validated in individuals with limb loss.…”
Section: Discussionmentioning
confidence: 96%